Anomalous Magnetic Field Activity During a Bioenergy Healing Experiment - Moga, Margaret M.; Bengston, William F. (Journal of Scientific Exploration, 2010)
A few studies have reported magnetic ﬁeld changes during bioenergy healing. In a pilot experiment, we examined magnetic ﬁ eld activity during hands-on healing and distant healing of mice with experimentally induced tumors. During healing sessions, we observed distinct magnetic ﬁeld oscillations adjacent to the mice cages, which were similar in appearance to those reported by Zimmerman (1985). The magnetic ﬁeld oscillations began as 20–30 Hz oscillations, slowing to 8–9 Hz, and then to less than 1 Hz, at which point the oscillations reversed and increased in frequency, with an overall symmetrical appearance resembling a “chirp wave.” The waves ranged from 1–8 milliGauss peak-to-peak in strength and 60–120 sec in duration. Evidence to date suggests that bioenergy healing may be detectable with DC gaussmeters, although we have not ruled out an artifactual basis for the oscillations reported here. Keywords: bioﬁeld—nonlocal effects—distant healing—ELF magnetic ﬁeld